SULPHUR (GANDHAKA) PURIFICATION METHODS W.S.R. TO RASA CLASSICS - Panigrahi, Debasis (Journal of Biomedical and Pharmaceutical Research, 2019)
Gandhaka is one of the materials that are in extensive use in the past and also in the present era. It can be equated with Sulphur in modern chemistry. All most all the Rasa literature have included it under UpaRasa group, however in the periodic table it belongs to VI – A. It has a great role mainly in the preparations of Rasa and Rasayana drugs. As such the material in crude form can’t be used in drug manufacturing and therefore the crude materials are to be subjected to certain pharmaceutical measures to render them suitable for conversion into medicine and among such procedures the Shodhana is one. Historically Shodhana concept was in existence since the time of Smriti grantha Manusmriti and Charak Samhita 1(600- 1000 B.C) as while enumerating the fundamentals of Ayurvedic Pharmaceutics- Saucha(Sudhhikarana) is found enumerated as one of the basic necessity for “Gunantaradhana”(alteration and/or addition of properties in the drugs). This concept was further developed after the development of Rasashastra. In the current article 18 classics of Rasashastra been explored and different Gandhaka Sodhana (purification) methods were analyzed and discussed elaborately. Keywords: Gandhaka,Sodhana,Dhalana, Bhavana, Prakshalana, Mardana, Nirvapa,Swedana, Galana